A Review Paper on Radial Basis Function for Solving Differential Equations - Aashna Gupta (Mathematical Statistician and Engineering Applications, 2022)
In this review paper, we will know how the radial basis function is used for solving the ordinary differential equation using neural network techniques. Also, how radial basis function is used for solving partial differential equations. Radial basis functions are commonly popular in solving PDEs as we can say that it is the most powerful method in the case of solving partial differential equations. Well, many radial functions are used for solving PDEs like the Kansas method, differential quadrature method, etc. there is always ongoing research in the field of development and a few new effective methods are also being used nowadays like global to local approximations which are known as localized methods and also to hybrid methods. But here we will majorly discuss the differential quadrature method for solving partial differential equations.